Factors Influencing University Students Using the Online Food Delivery in Malaysia - Hutabarat, Pauline Claudia; Tan, Celine; Shing, Tan Yan; Seng, Tee Wei (International Journal Of Tourism, 2023)
In this modern era, people need to find efficient solutions, especially for university students who have limited time constraints. This research paper will study the correlation between factors such as performance expectancy, effort expectancy, social influence, information quality, time-saving orientation, and price-saving orientation toward intention to use online food delivery for university students specifically in Malaysia. This paper adopted a framework from a previous research paper by Pitchay et al., (2021) which talks about topics that are in line but with a wider range of respondents. Respondents for this research paper are university students. Researchers want to test what influences this demographic to use online food delivery services. This paper also comes with solutions that can help the industry to enhance its business and attract more consumers. This paper uses the convenience sampling method to obtain data from various respondents; this is also due to the limitations of money and time in working on this research paper.